The future of newborn screening for lysosomal disorders. (24th August 2021) - Wasserstein, Melissa P.; Orsini, Joseph J.; Goldenberg, Aaron; Caggana, Michele; Levy, Paul A.; Breilyn, Margo; Gelb, Michael H.
Highlights: The goal of newborn screening is to improve the outcome of serious disorders. There is a wide range of innovative treatment options for LSDs. Multi-faceted approaches are being developed to enhance the accuracy of NBS. Data is needed to address potential ethical concerns associated with NBS for LSDs. Abstract: The goal of newborn screening is to enhance the outcome of individuals with serious, treatable disorders through early, pre-symptomatic detection. The lysosomal storage disorders (LSDs) comprise a group of more than 50 diseases with a combined frequency of approximately 1:7000. With the availability of existing and new enzyme replacement therapies, small molecule treatments and gene therapies, there is increasing interest in screening newborns for LSDs with the goal of reducing disease-related morbidity and mortality through early detection. Novel screening methods are being developed, including efforts to enhance accuracy of screening using an array of multi-tiered, genomic, statistical, and bioinformatic approaches. While NBS data for Gaucher disease, Fabry disease, Krabbe disease, MPS I, and Pompe disease has demonstrated the feasibility of widespread screening, it has also highlighted some of the complexities of screening for LSDs. These include the identification of infants with later-onset, untreatable, and uncertain phenotypes, raising interesting ethical concerns that should be addressed as part of the NBS implementation process. Taken together, these efforts will provide critical, detailed data to help guide objective, ethically sensitive decision-making about NBS for LSDs.